2018
DOI: 10.1007/s00213-018-4871-2
|View full text |Cite
|
Sign up to set email alerts
|

The hypocretin/orexin system as a target for excessive motivation in alcohol use disorders

Abstract: The hypocretin/orexin (ORX) system has been repeatedly demonstrated to regulate motivation for drugs of abuse, including alcohol. In particular, ORX seems to be critically involved in highly motivated behaviors, as is observed in high-seeking individuals in a population, in the seeking of highly palatable substances, and in models of dependence. It seems logical that this system could be considered as a potential target for treatment for addiction, particularly alcohol addiction, as ORX pharmacological manipul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 231 publications
(362 reference statements)
3
22
0
Order By: Relevance
“…These include differences in their anatomical distribution, with Hcrt/OX neurons denser in the medial area and MCH neurons denser in the lateral area of the LH (de Lecea et al, ; Sakurai et al, ), and also in their responses to the inflammatory agent liposaccharide (Palomba et al, ) and their coexpression of the peptide cocaine‐ and amphetamine‐regulated transcript (Jancsik et al, ). These Hcrt/OX and MCH neurons also differ in their functional activity, signaling through distinct electrical pathways to promote addictive‐like behaviors (DiLeone et al, ; Diniz and Bittencourt, ; Moorman, ). With the CXCL12/CXCR4 axis shown to modulate electrical excitability of peptide‐expressing neurons (Guyon et al, ), it may have differential effects on the signaling of Hcrt/OX and MCH neurons, with stronger effects on Hcrt/OX system due to its greater colocalization.…”
Section: Discussionmentioning
confidence: 99%
“…These include differences in their anatomical distribution, with Hcrt/OX neurons denser in the medial area and MCH neurons denser in the lateral area of the LH (de Lecea et al, ; Sakurai et al, ), and also in their responses to the inflammatory agent liposaccharide (Palomba et al, ) and their coexpression of the peptide cocaine‐ and amphetamine‐regulated transcript (Jancsik et al, ). These Hcrt/OX and MCH neurons also differ in their functional activity, signaling through distinct electrical pathways to promote addictive‐like behaviors (DiLeone et al, ; Diniz and Bittencourt, ; Moorman, ). With the CXCL12/CXCR4 axis shown to modulate electrical excitability of peptide‐expressing neurons (Guyon et al, ), it may have differential effects on the signaling of Hcrt/OX and MCH neurons, with stronger effects on Hcrt/OX system due to its greater colocalization.…”
Section: Discussionmentioning
confidence: 99%
“…With hcrt neurons known to interact with a number of different neurotransmitter systems (Elbaz et al., ), these EtOH‐induced changes in anatomical location are likely to alter the functional connectivity with these other systems. The fibers of hcrt neurons are found in zebrafish (Kaslin et al., ) and rats (Baimel and Borgland, ; Moorman, ) to project toward clusters of dopaminergic neurons, a circuit shown to mediate reward‐related behaviors (Baimel and Borgland, ). With the IH (Ren et al., ) and PT (Tay et al., ) in zebrafish known to contain dopaminergic neurons that regulate reward and are functionally homologous to the mammalian mesodiencephalic dopamine system (Kastenhuber et al., ), the increased presence and close proximity of hcrt neurons in these 2 areas in EtOH fish may facilitate their signaling with dopaminergic neurons, possibly more on the left side of the brain where positive stimuli are believed to promote reward behaviors (Davidson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypocretin/orexin (hcrt), an orexigenic neuropeptide expressed in a population of hypothalamic neurons, is known to be involved in promoting substance abuse and related behaviors such as increased EtOH consumption, arousal, anxiety, motivation, and stress (Li et al., ), suggesting that this neuropeptide is a potential therapeutic target for preventing the development of alcohol use disorder (Moorman, ). Studies in rats demonstrate that maternal EtOH consumption at low doses stimulates drinking in offspring and increases the expression and density of hcrt neurons (Chang et al., , ), and hypothalamic injection of this neuropeptide in adults increases EtOH intake and related emotional behaviors (Barson et al., ).…”
mentioning
confidence: 99%
“…With its varied behavioral effects, the precise underlying role of OX remains elusive. Several laboratories have hypothesized that OX serves to promote motivation in highly salient environmental contexts, and have suggested that an OX-based pharmacotherapy could be ideal for treating behaviors like reinstatement of extinguished drug seeking (Espana 2012, James et al 2017, Moorman 2018, as it would affect excessive but not homeostatic behavior. Interestingly, research reviewed here on the role of OX in feeding, even dysregulated feeding that resembles addiction, indicates that the conditions under which OX promotes this behavior are different than those under which it promotes drug use.…”
Section: Introductionmentioning
confidence: 99%